2022
DOI: 10.1186/s12859-022-04934-1
|View full text |Cite
|
Sign up to set email alerts
|

Mining on Alzheimer’s diseases related knowledge graph to identity potential AD-related semantic triples for drug repurposing

Abstract: Background To date, there are no effective treatments for most neurodegenerative diseases. Knowledge graphs can provide comprehensive and semantic representation for heterogeneous data, and have been successfully leveraged in many biomedical applications including drug repurposing. Our objective is to construct a knowledge graph from literature to study the relations between Alzheimer’s disease (AD) and chemicals, drugs and dietary supplements in order to identify opportunities to prevent or de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…To accomplish this task, corrections are required, such as data cleaning, identification and management of outliers, handling of missing data, and correction of errors in the information. These actions ensure the consistency and reliability of the data, thus establishing a solid basis for moving forward in the analysis process [34], [35]. The information collected in our research will be subjected to this phase to ensure that the data obtained is reliable and of high quality, thus allowing the transition to the next stage, which is modeling.…”
Section: Modifymentioning
confidence: 98%
“…To accomplish this task, corrections are required, such as data cleaning, identification and management of outliers, handling of missing data, and correction of errors in the information. These actions ensure the consistency and reliability of the data, thus establishing a solid basis for moving forward in the analysis process [34], [35]. The information collected in our research will be subjected to this phase to ensure that the data obtained is reliable and of high quality, thus allowing the transition to the next stage, which is modeling.…”
Section: Modifymentioning
confidence: 98%
“…Experiments showed that iDPath could identify explicit critical paths that were consistent with clinical evidence. Nian et al [67] utilized semantic triples in SemMedDB for KG construction and drug-disease link prediction. They filtered the most relevant semantic triples for Alzheimer's disease (AD) using a BERT-based classifier and some rule-based methods, and trained graph embedding algorithms, such as TransE [68], DistMult [69], and ComplEx [70], to predict drug/chemical/ food supplement candidates that may be helpful for AD treatment or prevention.…”
Section: In Silico Drug Repurposingmentioning
confidence: 99%
“…Zhu [34]'s work exemplifies this trend by creating diseasespecific knowledge graphs, including for AD, from PubMed abstracts, employing advanced models like Att-BiLSTM-CRF [35] for named entity recognition and a combination of BiLSTM [36] and ResNet [37] for relation extraction. Similarly, Nian [38]'s research utilizes literaturederived knowledge graphs, extracting AD-related triplets from SemMedDB [39,40] to explore connections between AD and various entities, showcasing the growing emphasis on data-driven methodologies in constructing knowledge graphs for AD research.…”
Section: Introductionmentioning
confidence: 99%